Fauna and biotopic distribution of weevils (Coleoptera: Curculionoidea) of the Zhiguli State Nature Reserve, Russia - Dedyukhin, Sergei V. (Nature Conservation Research: Заповедная наука, 2022)
Curculionoidea (hereinafter – weevils) comprises the largest group of phytophagous beetles. They are an integral component of terrestrial and freshwater communities and are associated with a wide range of plants. Therefore, weevils can serve as one of the model taxa for assessing the diversity and specificity of biota, including those in Protected Areas of various ranks. This article is based on the results of original studies (in 2011, 2013, 2014, 2021) and a critical review of literature sources. The species composition was identified, and the characteristics of the weevil fauna of the Zhiguli State Nature Reserve (Samara Region, Russia) was carried out. The weevil fauna of the Zhiguli State Nature Reserve is characterised by a very high species richness and considerable originality. As a result of research, 355 species from five families of this group were identified. Of these, 66 species were recorded for the first time in the Zhiguli State Nature Reserve, including 52 species that were recorded for the first time in the fauna of the Samara Region. In terms of the number of species, the studied fauna considerably exceeds similar faunas of Protected Areas in the forest-steppe of the Southern Urals and is twice as rich as the faunas of Protected Areas of the southern steppe in the Orenburg Region. It is characterised by a complex composition, which is caused by sympatry of species of European, Siberian and Kazakh-Turanian faunas (including narrow endemics of the River Volga Region and a heterogeneous group of relicts), and steppe, nemoral and boreal forms in the study area. In the Zhiguli State Nature Reserve, we distinguished weevil complexes of forb-feather-grass steppes (120 species) and petrophytic steppes (113 species), broad-leaved (117 species) and pine (97 species) forests, floodplain and islands of the River Volga (92 species), as well as ruderal habitats (126 species). Trophically specialised weevil species of the Zhiguli State Nature Reserve are associated with plants from 34 families. The largest number of weevil species were found on Fabaceae (66 species), Asteraceae (39 species) and Brassicaceae (27 species). In general, the weevil fauna of the Zhiguli State Nature Reserve can be considered as a reference for the forest-steppe of the Volga Upland, which confirms its great importance for the preservation of the original natural ecosystems of the Middle Volga Region.